The sword in early medieval Northern Europe experience, identity, representation - Brunning, Sue ca. 20./21. Jh (Anglo-Saxon studies, 2019)
A wide-ranging study of the significance of swords throughout the whole Anglo-Saxon period, offering valuable insights into the meaning of and attitude towards swords